2011
DOI: 10.1002/bjs.7559
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent groin hernia surgery

Abstract: The laparoscopic and the open preperitoneal mesh methods of repair for recurrent groin hernias were associated with the lowest risk of reoperation. Although the method of repair in previous surgery must be considered, these techniques are the preferred methods for recurrent groin hernia surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 71 publications
(82 reference statements)
2
32
0
4
Order By: Relevance
“…13-60 Lichtenstein procedure was described in 8 NRCT (3 case series studies, 5 observational) including 15,121 patients versus 5 RCTs including 291 patients (Table 2). 15,[22][23][24]38,39,46,47,50,59,[61][62][63] Fifteen prospective trials were identified. 13,15,16,18,25,[39][40][41]44,[48][49][50]52,55,59,61 The analysis, due to missing data in the included trials, was limited to outcomes providing comprehensive information.…”
Section: Resultsmentioning
confidence: 99%
“…13-60 Lichtenstein procedure was described in 8 NRCT (3 case series studies, 5 observational) including 15,121 patients versus 5 RCTs including 291 patients (Table 2). 15,[22][23][24]38,39,46,47,50,59,[61][62][63] Fifteen prospective trials were identified. 13,15,16,18,25,[39][40][41]44,[48][49][50]52,55,59,61 The analysis, due to missing data in the included trials, was limited to outcomes providing comprehensive information.…”
Section: Resultsmentioning
confidence: 99%
“…Repeat endoscopic repair is only feasible when the surgeon has a high level of experience in repeat endoscopic groin hernia repair [26]. However, registry data show that even following previous open suture and mesh repair to treat the primary inguinal hernia, open suture and mesh repair are used once again for a recurrent hernia [27]. That is due to the fact that the skill needed for laparo-endoscopic recurrent inguinal hernia repairs was not always assured.…”
mentioning
confidence: 99%
“…The followup periods in this study also varied widely. Usually, the recurrence rate is estimated as twice the number of reoperations [31] the reoperation rates following TEP laparoscopic hernioplasty and Lichtenstein hernioplasty were 3.3% and 2.4%, respectively [32]. It therefore suggests that the recurrence rates were around 6.6% and 4.8% for the laparoscopic and Lichtenstein hernioplasties, respectively.…”
Section: Discussionmentioning
confidence: 99%